Research in the history of economic thought and methodology. Vol. 39B Pt. B : including a symposium on Carl Menger at the centenary of his death - Scheall, Scott; Fiorito, Luca; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology., 2021)
Volume 39B of Research in the History of Economic Thought and Methodology, includes a symposium marking the centenary of Carl Menger's death in 1921. The symposium, edited by Reinhard Schumacher and Scott Scheall, features contributions from Sandra J. Peart, Günther Chaloupek, Erwin Dekker, and Sandye Gloria. The Volume also features general-research essays from Marina Uzunova and Alexander Linsbichler.